Dimorphic growth and molecular characterization of Candida guillermondi isolated from Pannicum maximun - Rosales-López, Catalina (2018)
Candida guilliermondii is an ascomicete yeast widely distributed in the natural environment, this yeast is attributed several properties that make it be of biotechnological interest, such as for biological control. In this project C. guillermondii was isolated from Panicum maximun grass, collected in soccer squares, street edges and pastures of the areas of Cartago and Heredia. Small, ovoid and budding colonies, 3 to 5 μm and cream colored, were purified at 48 h of culture at 25 ° C in PDA. They were grown in liquid medium, to stimulate the growth of biomass and to be able to carry out the molecular analysis, the DNA was extracted and the PCR tests with different primers were realized. The sequences generated were compared by alignment using the Blast tool from the National Center for Biotechnology Information (NCBI) and compared to the Gen Bank database, identifying Candida guillermondii. Pseudohyphae induction was carried out. Different culture conditions were tested: light, temperature and pH, and several culture media (carbon sources, nitrogen, medium poor in minerals and medium with only agar-water). Well-developed pseudomyelium formation was achieved from 96 h of incubation, pH and light, media such as water agar, supplemented with sucrose, which did not contain nitrogen source and Vogels, were determinants for the appearance of hyphae in the yeasts. Concluding that causing stress to the microorganism allows a morphological change in it.